Interethnic interaction of Russian and Tuvans in Soviet and Post-Soviet Tuva: the case of ethnically mixed families - Zoya Yu. Dorzhu (Novye issledovaniâ Tuvy, 2019)
The article analyzes issues of interethnic marriages between Tuvans and Russians in the Republic of Tuva, which are considered as one of the aspects of interethnic contact between the two largest ethnic groups in the region. The chronological frames of the study are the Soviet (1944-1991) and post-Soviet (since 1991) periods. For its sources, the study looks at statistical data for the years 1979, 1989, 2002, 2007 and 2010, also focusing on data from a survey of Kyzyl residents of different ethnic backgrounds, done by the author in March and April 2017. An additional source is found in personal observations and materials of interviews held in 2015-2018 with 20 respondents aged over 65 and in interethnic marriage. The history of Tuvan – Russian interaction spans two centuries, and it has had its impact on demographic processes. While in the past Tuvans had preferred intra-ethnic marriage, it was the change in the demographic situation and interethnic integration which led to the rise of interethnic marriage. The article examines the dynamics of such marriages, spouses’ motivation and reasons for  choosing a partner, the reaction of their milieus, and the problem of children in ethnically mixed families. The mixed family brought about new features in culture, home life, and traditions, which differentiated its new lifestyle from that of the single-ethnic family, where the spouses grew up. Meanwhile, processes of linguistic  communication within the family led to increased bilingualism as well as to strengthening of new kinship ties which ensured the ethnopolitical stability of the multiethnic region. While mixed families are still frequent in contemporary Tuva, the public attitude towards such marriages has changed to the opposite. Negative attitude to interethnic marriages is due to differences in religion, as well as in traditions and customs. Since these factors are likely to generate intrafamily controversies, such marriages are increasingly regarded as unstable. The strengthening of nationalist tendencies in post-Soviet society also played a big role.